PEREMPUAN DALAM SASTRA LISAN PULAU RAAS: KAJIAN GENDER - Anas Ahmadi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
Studies on the relationship between women and oral literature have been interesting topics to be discussed. This paper, therefore describes Raas Island Oral Literature (RIOL) or Sastra Lisan di Pulau Raas (SLPR) by focusing on women fromgender perspective. The design of this study is qualitative research by gathering oral literature data in Raas Island. The data were collected by conducting observation, video recording, tape recording, taking notes and interviewing. The result of the analysis showed that SLPR corresponds to marginalized women which arerepresented in the puzzle (bhag-tebhgan), proverd (parebhasan), and folktale (caretarakyat). The women, through SLPR, are portrayed as weak creatures, sex objects andsluts.